The foreign trade pattern and foreign trade specialization of candidates of the European Union - Bahri Yilmaz; Selim Jürgen Ergun (Free University Berlin, Jean Monnet Centre of Excellence, 2003)
The enlargement of the European Union will bring many political, economical and structural changes on the Continent, which require careful and deep analysis to be made. This paper will grasp the enlargement of the European Union from the aspect of the trade pattern and trade specialization of six major European Union candidates; namely, Turkey, Bulgaria, Hungary, Romania, Poland and the Czech Republic by focusing on the years from 1996 to 2002. In other words, the main purpose of this paper is to examine the international competitiveness of six candidate countries and to compare the structure of specialization in foreign trade with each other and the EU/15.
Keywords: F17; F02; F15; 330; Trade and FDI; Economic Integration; Aussenhandelsstruktur; Internationale Arbeitsteilung; Internationaler Wettbewerb; EU-Erweiterung; Türkei; Bulgarien; Rumänien; Polen; Tschechische Republik; EU-Staaten